Beyond the PDF: Expanding Art History Digitally with British Art Studies. (3rd April 2019) - Card, Baillie; Droth, Martina; Scutt, Tom; Turner, Sarah Victoria
Abstract : British Art Studies, a born-digital, open-access journal, co-published by the Paul Mellon Centre for Studies in British Art (PMC) and the Yale Center for British Art (YCBA), launched in November 2015. This article documents how and why British Art Studies was established and the ethos that has motivated the editorial team to always think "beyond the PDF" in creating a new digital publication for the field of art history. Drawing on case studies of articles and features published in the first seven issues of British Art Studies, the purpose of this article is to reflect on the creation and development of the journal alongside the broader critical and methodological questions that have guided and shaped our approach to publishing. Co-written by the current editorial and production team, this article explores how establishing and maintaining British Art Studies has enabled us and our authors to join the growing conversation about the intersection and cross-fertilization of art-historical research with digital tools and technologies.